Comprehensive analysis of the cytokine-rich chromosome 5q31.1 region suggests a role for IL-4 gene variants in prostate cancer risk - Tindall, E A; Severi, G; Hoang, H N; Ma, C S; Fernandez, P; Southey, M C; English, D R; Hopper, J L; Heyns, C F; Tangye, S G; Giles, G G; Hayes, V M (Carcinogenesis (New York), 2010)
Although inflammation is emerging as a candidate prostate cancer risk factor, the T-helper cytokine-rich [interleukins (IL)-5, 13 and 4] chromosomal region at 5q31.1 has been implicated in prostate cancer pathogenesis. In particular, IL-4 has been associated with prostate cancer progression, whereas the IL-4 -589C>T (rs2243250) promoter variant has been associated with differential gene expression. We genotyped rs2243250 and 11 tag single-nucleotide polymorphisms (SNPs) spanning 200 kb across the 5q31.1 region on 825 cases and 732 controls from the Risk Factors for Prostate Cancer Study. The minor alleles of rs2243250 and an IL-4 tagSNP rs2227284 were associated with a small increase in prostate cancer risk. Per allele odds ratios (ORs) are 1.32 [95% confidence interval (CI) 1.08-1.61, P = 0.006] and 1.26 (95% CI 1.07-1.48, P = 0.005), respectively. Although these associations were not replicated in an analysis of the Melbourne Collaborative Cohort Study, including 810 cases and 1733 controls, no clinicopathological characteristic was implicated for this divergence. Correlating rs2243250 genotypes to IL-4 gene transcript levels and circulating IL-4 plasma levels, we observe in contrast to previous reports, a non-significant trend toward the minor T-allele decreasing the likelihood of IL-4 activity. From our observed association between a low IL-4 producing promoter T-allele and prostate cancer risk, our study suggests an antitumor role for IL-4 in prostate cancer. Although we saw no association for IL-5 or IL-13 gene variants and prostate cancer risk, our findings call for further evaluation of IL-4 as a contributor to prostate cancer susceptibility.